Neo-Pragmatism: Implications for Research and Teaching - Stewart, David (School of Management Working Papers, 2011)
The marketing discipline is facing a number of challenges, namely the encroachment of the marketing arena by other disciplines, the role of consumer behaviour, the academic practitioner gap, and the postmodern condition. For those involved in the marketing discipline, these challenges can be dissipated by adopting neo-pragmatism as a research protocol. Neopragmatism, based on the linguistic turn in modern philosophy, is anti-foundational, antiessentialism, but accepts rationality within a specific context and historical epoch. Ontology and epistemology are collapsed, and replaced by ontological hermeneutics with the goal of developing understanding by exploring praxis. This leads to marketing-as-practice being the research endeavour. Such an approach is concerned with how marketing is done, so the focus is on how individuals think, speak, politicise and routinely interact within the work place. This has implications for research and teaching, where the move is away from prescriptive models and generalizations to insights gained from an understanding of practical actions within a given context.